Patients With Triangular Fibrocartilage Complex Injuries and Distal Radioulnar Joint Instability Gain Improved Forearm Peak Pronation and Supination Torque After Reinsertion. (March 2020) - Andersson, Jonny K.; Hagert, Elisabet M.; Fridén, Jan
Background: Forearm peak pronation and supination torque measurements are reduced up to 30% in patients with triangular fibrocartilage complex (TFCC) 1B injuries with concomitant distal radioulnar joint (DRUJ) instability. The aim of our study was to evaluate whether patients with TFCC 1B injuries, with concomitant DRUJ instability, improve in forearm peak pronation and supination torque following TFCC reinsertion surgery where postoperative DRUJ stability was achieved.Methods: We report a retrospective case series with short-term follow-up (20 months) of the postoperative forearm peak torque in pronation and supination in 11 patients (9 women/2 men, average age at surgery 32 years) operated on by TFCC reinsertion. Two of the initial 13 patients were later on reoperated due to recurring DRUJ instability and were therefore excluded in this follow-up study. Nine were treated by arthroscopic TFCC reinsertion and 2 by open technique. The forearm peak pronation and supination torque were measured pre- and postoperatively and compared with the uninjured side.Results: On average, a 16% improvement of the forearm peak torque was achieved in the injured wrist, as well as clinically assessed DRUJ stability. Functional postoperative improvement was noted in all patients, with reduced pain, good satisfaction, and acceptance of the surgery and the final result.Conclusion: We conclude that patients with TFCC injuries and DRUJ instability gain improved forearm peak pronation and supination torque after reinsertion. We also conclude that forearm peak pronation and supination torque is a valuable tool in the preoperative diagnostics of TFCC injuries with DRUJ instability as well as in the postoperative follow-up.